Circular RNA circFGFR1 promotes progression and anti-PD-1 resistance by sponging miR-381-3p in non-small cell lung cancer cells - Zhang, Peng-Fei (Mol Cancer, 2019)
BACKGROUND: Immune system evasion, distance tumor metastases, and increased cell proliferation are the main reasons for the progression of non-small cell lung cancer (NSCLC) and the death of NSCLC patients. Dysregulation of circular RNAs plays a critical role in the progression of NSCLC; therefore, further understanding the biological mechanisms of abnormally expressed circRNAs is critical to discovering novel, promising therapeutic targets for NSCLC treatment. METHODS: The expression of circular RNA fibroblast growth factor receptor 1 (circFGFR1) in NSCLC tissues, paired nontumor tissues, and cell lines was detected by RT-qPCR. The role of circFGFR1 in NSCLC progression was assessed both in vitro by CCK-8, clonal formation, wound healing, and Matrigel Transwell assays and in vivo by a subcutaneous tumor mouse assay. In vivo circRNA precipitation, RNA immunoprecipitation, and luciferase reporter assays were performed to explore the interaction between circFGFR1 and miR-381-3p. RESULTS: Here, we report that circFGFR1 is upregulated in NSCLC tissues, and circFGFR1 expression is associated with deleterious clinicopathological characteristics and poor prognoses for NSCLC patients. Forced circFGFR1 expression promoted the migration, invasion, proliferation, and immune evasion of NSCLC cells. Mechanistically, circFGFR1 could directly interact with miR-381-3p and subsequently act as a miRNA sponge to upregulate the expression of the miR-381-3p target gene C-X-C motif chemokine receptor 4 (CXCR4), which promoted NSCLC progression and resistance to anti-programmed cell death 1 (PD-1)- based therapy. CONCLUSION: Taken together, our results suggest the critical role of circFGFR1 in the proliferation, migration, invasion, and immune evasion abilities of NSCLC cells and provide a new perspective on circRNAs during NSCLC progression.